ORAL SPEECH AND ITS DEVELOPMENT FEATURES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, the role of speech in the formation of personality, the principles of the formation of the skills of analyzing speech into sounds in students, the methods of modern literacy based on the researches of psychologists, and the perception of oral speech for children with hearing impairment. It is written about teaching.